Toxicity of copper hydroxide nanoparticles, bulk copper hydroxide, and ionic copper to alfalfa plants: A spectroscopic and gene expression study - Martinez-Martinez, Alejandro (2018)
Bulk Cu compounds such as Cu(OH)2 are extensively used as pesticides in agriculture. Recent investigations suggest that Cu-based nanomaterials can replace bulk materials reducing the environmental impacts of Cu. In this study, stress responses of alfalfa (Medicago sativa L.) seedlings to Cu(OH)2 nanoparticle or compounds were evaluated. Seeds were immersed in suspension/solutions of a Cu(OH)2 nanoform, bulk Cu(OH)2, CuSO4, and Cu(NO3)2 at 25 and 75 mg/L. Six days later, the germination, seedling growth, and the physiological and biochemical responses of sprouts were evaluated. All Cu treatments significantly reduced root elongation (average = 63%). The ionic compounds at 25 and 75 mg/L caused a reduction in all elements analyzed (Ca, K, Mg, P, Zn, and Mn), excepting for S, Fe and Mo. The bulk-Cu(OH)2 treatment reduced K (48%) and P (52%) at 75 mg/L, but increased Zn at 25 (18%) and 75 (21%) mg/L. The nano-Cu(OH)2 reduced K (46%) and P (48%) at 75 mg/L, and also P (37%) at 25 mg/L, compared with control. Confocal microscopy images showed that all Cu compounds, at 75 mg/L, significantly reduced nitric oxide, concurring with the reduction in root growth. Nano Cu(OH)2 at 25 mg/L upregulated the expression of the Cu/Zn superoxide dismutase gene (1.92-fold), while ionic treatments at 75 mg/L upregulated (∼10-fold) metallothionein (MT) transcripts. Results demonstrated that nano and bulk Cu(OH)2 compounds caused less physiological impairments in comparison to the ionic ones in alfalfa seedlings.